A Model of Dynamic Takeover Behavior - GIAMMARINO, RONALD M.; HEINKEL, ROBERT L. (Journal of Finance, 1986)
ABSTRACT Several observed features of takeover contests appear to be inconsistent with value‐maximizing behavior on the part of the agents involved. For instance, managers occasionally resist takeover bids, presumably in order to facilitate competition among bidders. However, counterbids do not always materialize, suggesting that management resistance was not in the best interests of the firm's shareholders. On the other hand, a successful takeover is sometimes accompanied by a decrease in the value of the acquirer's shares. In addition, valuable combinations are occasionally not consummated. We present a simple illustration of sequential takeover bidding in which all managers act in the best interests of their respective shareholders. Within the context of this model, we provide an explanation of the type of behavior described above.